Treatment of Metastatic Primary Extramammary Paget Disease With Combination Anlotinib and Tislelizumab: A Case Report and Review of the Literature - Yin, Xin; Li, Xiaoqing; Li, Muli; She, Qing; Liu, Yan; Chen, Xiaodan; Ma, Suhua; Ma, Qian; Huang, Zhangkan; Xu, Lin; Huang, Xiaozhun; Zhan, Zhengyin; et al. (Frontiers in Medicine, 2022)
Extramammary Paget’s disease (EMPD) is a rare cutaneous neoplasm with distant metastases and poor prognosis. We report the case of a 63-year-old male patient exhibiting stage IV primary EMPD with neuroendocrine differentiation, and harboring a somatic mutation in AMER1. After four cycles of Anlotinib combined with Tislelizumab, the patient achieved partial response for the metastatic lesions according to mRECIST1.1 criteria. Total positron emission tomography and computed tomography (PET-CT) scans revealed a significant reduction in SUV from 18.9 to 5.3, and the serum CEA decreased to normal levels after the treatment regimen. However, the patient developed fractures of the fourth and fifth thoracic vertebrae during the treatment. Therefore, percutaneous vertebroplasty was performed, and the patient experienced severe postoperative pneumonia and died from pulmonary encephalopathy and respiratory failure in June, 2021. The overall and progression-free survival of the patient after diagnosis were 9 months and 8 months respectively. During the systemic treatment, the patient suffered grade 1 rash in the back and thigh and grade 1 hypertension. Nevertheless, the combination treatment of Anlotinib and Tislelizumab had a favorable clinical outcome and provided a survival advantage, and should be considered a therapeutic option for patients with AMER1-mutant metastatic EMPD.